Mainstreaming Eco-Industrial Parks - Kechichian, Etienne; Jeong, Mi Hoon (World Bank, Washington, DC, 2016)
Special Economic Zones have played an important role in the economic growth of many developing and advanced-developing nations, including Bangladesh, Brazil, India, Republic of Korea, Thailand, Turkey and Vietnam. These zones provide tailored infrastructure and business services, and they have become a successful model for large-scale job creation, transfer of skills and technology, export diversification, and industrial development led by foreign direct investment. In the next era of industrial zone development, sustainability and eco-industrial growth play paramount roles in minimizing environmental and social risks while generating profits for firms. It has become urgent to explore these models and to understand the contexts in which they can tackle the environmental and ecological challenges of our times while retaining their role as production hubs and growth centers. This report, based primarily on a global conference Eco-Industrial Parks (EIP) 2015, held in Seoul, Republic of Korea in October 2015, provides the latest thinking on eco-industrial parks, bringing together experiences from different countries and providing a vision on how these initiatives can be scaled up or mainstreamed. It will provide policy makers with insight conceptualizing EIPs and what different factors need to be considered in putting together an EIP program. The report builds the basis for further development of guidelines and step-by-step approaches on how to develop a national program on EIPs.